FORMULASI OBAT KUMUR EKSTRAK KULIT PISANG KEPOK KUNING (Musa paradisiaca L.) SEBAGAI ANTIBAKTERI - Julyanti, Ai Rian; Genatrika, Erza; Annissya, Widia Primi; Setyaningrum, Nenden; Ferliati, Rosi Eka; Pratama, Okta Nurandi (Jurnal Buana Farma, 2024)
Yellow kepok banana peel (Musa paradisiaca L.) contains alkaloid, flavonoid, and tannin compounds that are known to have antibacterial activity. This study was conducted to determine the antibacterial activity of mouthwash from yellow kepok banana peel in inhibiting the growth of Streptococcus mutans. The yellow kepok banana peel used the maceration method with 96% ethanol solvent, then mouthwash preparation formulations with the extract concentrations of 2%, 4%, and 8%. The antibacterial activity of the mouthwash preparation was tested against Streptococcus mutans using the disc diffusion method. The results showed that the mouthwash formula of yellow kepok banana peel extract had inhibitory power on Streptococcus mutans bacteria with an inhibition zone of 9.52 mm in formula I, formula II 10.67 mm, and formula III 12.36 mm. Formulas I and II are classified as moderate antibacterial activity categories, while formula III is classified as having strong antibacterial activity. The results showed a p <0.05, meaning each test group has a significant difference. Formula III is the best formula because the resulting preparation is homogeneous, PH is 5, viscosity is 2.4 cP, the preparation is stable and formula III has the best antibacterial activity.